2021
DOI: 10.3390/ijms22105111
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Platinum-Based Anticancer Drugs to Overcome Gliomas

Abstract: Although there are many patients with brain tumors worldwide, there are numerous difficulties in overcoming brain tumors. Among brain tumors, glioblastoma, with a 5-year survival rate of 5.1%, is the most malignant. In addition to surgical operations, chemotherapy and radiotherapy are generally performed, but the patients have very limited options. Temozolomide is the most commonly prescribed drug for patients with glioblastoma. However, it is difficult to completely remove the tumor with this drug alone. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 218 publications
0
16
0
Order By: Relevance
“…Therefore, the restricted intranasal delivery of Pt-based drugs can be anticipated in the treatment of GB. To date, few studies have reported to evaluate the in vivo performance of Pt-based agents against GB, although their significance has been recognized to repurpose or reposition the existing chemotherapeutic drugs for GB treatment [ 56 , 57 ]. In the sparse reports, only two cases administered the Pt agents via IN route, all about nanoformulations based on either carboplatin or FePt alloy nanoparticles [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the restricted intranasal delivery of Pt-based drugs can be anticipated in the treatment of GB. To date, few studies have reported to evaluate the in vivo performance of Pt-based agents against GB, although their significance has been recognized to repurpose or reposition the existing chemotherapeutic drugs for GB treatment [ 56 , 57 ]. In the sparse reports, only two cases administered the Pt agents via IN route, all about nanoformulations based on either carboplatin or FePt alloy nanoparticles [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Platinum application as an anticancer agent is widely known, especially due to cis-platinum and its derivatives. The usefulness of complexed platinum drugs is severely limited by serious systemic toxicity that is induced in a dose-dependent manner [ 1 ]. The development of new nanoplatforms, which could modify the biological disposition of Pt compounds, reduce its toxicity and perhaps attenuate the undesirable side effects, is one of the most challenging tasks in experimental oncology to date [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the majority of patients with GBM experience tumor recurrence, and recurrent tumors commonly show a poor response to standard therapy [ 6 ]. Despite advancements in the understanding of GBM molecular diagnosis and ongoing trials on targeted therapies, standard therapy has not advanced over the past two decades [ 7 ].…”
Section: Introductionmentioning
confidence: 99%